(untitled) (Fiep Bulletin - online, 2014)
This study presents an issue that has been worrying parents and educators: the use of drugs. In order to expand the Physical Education field experience, we have gone in search of a theme that could relate physical activity to recovery from drug addiction. With this, we want to make a contribution to this field with theorical and methodological reflections on drug dependency. The method used was based on a qualitative research paradigm with case study. For that, we have also used half-structuralized interview, non-participating observance and documentary analysis. The experimental group was composed of seven drug users in chemical dependence treatment in a therapeutic community in the city of Novo Hamburgo. We have concluded that the activities practiced by the patients have contributed to their mental health, well-being, self-esteem, wellness and sleep.